Temperature-dependent feeding behavior in the brown box crab, Lopholithodes foraminatus - Moretto, Wave I.; Taylor, Jennifer R. A. (Frontiers in Marine Science, 2023)
Growing fishing pressures and ocean warming are potential concerns for populations of brown box crabs, Lopholithodes foraminatus, at the southern end of their geographic distribution. In Southern California, brown box crabs are thought to occupy a broad depth gradient (intertidal zone -547 m), which exposes them to temperatures ranging from 8℃ -24°C. This large temperature span presents challenges for these ectothermic animals because the rates of their physiological processes, and ultimately their dietary needs, behavior, and health, vary with temperature. Here we examined how temperature affects the feeding behavior of brown box crabs to better understand their ecology in warmer regions of their distribution. Adult crabs were exposed to one of three temperature treatments (8℃, 15°C, and 20℃, N=10) for 2 months. Weekly throughout the exposure period, crabs were given two similar-sized prey items of different crushing strength (clam and mussel). Claw pinch force, prey preference, time to consume prey, and number of prey consumed were recorded prior to the start of the experiment and weekly for the duration of the study, with the exception of pinch force, which was recorded bi-weekly. We hypothesized that crabs will have a stronger pinch force at warmer temperatures, prefer prey items that require less breaking force at the coldest temperature, consume prey faster at warmer temperatures, and consume more prey at warmer temperatures. Our results confirm that pinch force is consistently greater at 15°C compared to 8°C, however, crabs at 8°C consumed more clams (higher strength) while those at 15°C consumed more mussels. Crabs at 8°C also consumed prey items faster than crabs at 15°C but ate a similar number of prey. Furthermore, there was 100% mortality at 20℃ within 8 days of exposure, indicating their proximity to lethal limits within Southern California. These results show that brown box crab feeding behavior exhibits temperature thresholds, which may alter their nutritional state, community interactions, and distribution under both short-term and long-term changes in ocean temperature.